2021
DOI: 10.1002/ccr3.4890
|View full text |Cite
|
Sign up to set email alerts
|

CT patterns and differential criteria for acute eosinophilic pneumonia and COVID‐19 pneumonia

Abstract: Difficulties encountered in diagnosing and treating COVID‐19 pneumonia and acute eosinophilic pneumonia during the pandemic from 2019 to 2021 led to the identification and study of the differential features of the two conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…It is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). [1][2][3][4][5][6][7][8] Additionally, it has been shown that patients with concomitant chronic illnesses had a greater mortality risk during the pandemic. 9 Angiotensin (Ang) converting enzyme type 2 (ACE2) is expressed on the surface of numerous human cells and shows the affinity of the SARS-CoV-2 S-peptide to this ACE2.…”
Section: Introductionmentioning
confidence: 99%
“…It is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). [1][2][3][4][5][6][7][8] Additionally, it has been shown that patients with concomitant chronic illnesses had a greater mortality risk during the pandemic. 9 Angiotensin (Ang) converting enzyme type 2 (ACE2) is expressed on the surface of numerous human cells and shows the affinity of the SARS-CoV-2 S-peptide to this ACE2.…”
Section: Introductionmentioning
confidence: 99%